PENGARUH EMPLOYEE EMPOWERMENT TERHADAP EMPLOYEE PERFORMANCE DENGAN EMPLOYEE ENGAGEMENT SEBAGAI MEDIASI - Dhita Hafizha Asri (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Employee empowerment and engagement greatly affect employee performance. Employee dissatisfaction with the company can lead to undesirable behaviors. Employee empowerment and engagement have an important role in getting high productivity in employees and supporting company goals. The purpose of this study was to determine how the effect of employee empowerment on employee performance with employee involvement as a mediating variable. This research is quantitative by using cross-sectional study. The population in this study were bank employees in the city of Batam with a sample size of 344 people. Samples were obtained by using quota sampling technique. Data collection using a questionnaire and processed with the PLS application. The results of this study indicate that employee empowerment and employee involvement as a mediator determine significantly the employee’s performance